A randomized controlled trial to compare the effectiveness and safety of adsorbent lotion containing tapioca starch, spent grain wax, Butyrospermum parkii extract, argania spinosa kernel oil, aloe barbadensis, rosehip oil, and allantoin with a low-potency topical corticosteroid in the treatment of intertrigo - Leeyaphan C. (2023)
Background: Intertrigo is an inflammatory skin-fold condition. Candida infections may occur concurrently or afterward. Topical corticosteroids may reduce inflammation but exacerbate Candida infections. The treatment is contentious. Objective: To evaluate the efficacies and safety of adsorbent lotion containing tapioca starch, spent grain wax, Butyrospermum parkii extract, argania spinosa kernel oil, aloe barbadensis, rosehip oil, and allantoin for the treatment of mild-to-moderate intertrigo, relative to 1% hydrocortisone cream. Methods: This randomized, double-blinded study enrolled 40 intertrigo patients. Twice daily, 20 patients applied adsorbent lotion while the remainder used 1% hydrocortisone cream. Efficacy evaluation, skin biophysical measurements, skin tolerability, safety, and visual analog scale (VAS) patient-satisfaction scores were evaluated at baseline and Week 2. Results: The adsorbent lotion showed higher complete cure rates for color, partial epidermal loss, papules/pustules/vesicles/patches, dryness, and scaling than the corticosteroid without statistical significance. Adsorbent lotion demonstrated significantly higher reduction in pruritus than the corticosteroid treatment. Reduction of erythema level using Mexameter and VAS patient-satisfaction scores were not statistically different between adsorbent lotion and hydrocortisone cream. No adverse effects or superimposed infections were reported. Conclusions: The anti-inflammatory efficacies of adsorbent lotion and low-potency steroid were equivalent. The lotion was safe and produced excellent pruritus reduction. Patient satisfaction was high.